2007
DOI: 10.1161/circresaha.106.146670
|View full text |Cite
|
Sign up to set email alerts
|

Knock-In Mouse Model of Dilated Cardiomyopathy Caused by Troponin Mutation

Abstract: Abstract-We created knock-in mice in which a deletion of 3 base pairs coding for K210 in cardiac troponin (cTn)T found in familial dilated cardiomyopathy patients was introduced into endogenous genes. Membrane-permeabilized cardiac muscle fibers from mutant mice showed significantly lower Ca 2ϩ sensitivity in force generation than those from wild-type mice. Peak amplitude of Ca 2ϩ transient in cardiomyocytes was increased in mutant mice, and maximum isometric force produced by intact cardiac muscle fibers of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
208
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(238 citation statements)
references
References 30 publications
30
208
0
Order By: Relevance
“…The severity of the HCM phenotype does not seem to be dependent on the R21C mutant gene dosage because ϳ25% of the total cTnI is mutated in the heterozygotes and is sufficient to promote a similar hypertrophic response to that of the homozygous mice. Nevertheless, previous studies have shown that an increase in the ratio of mutant to WT protein in vivo and in vitro within myofilaments can lead to larger phenotypic and/or lethal effects (43). Therefore, in vivo hemodynamic and echocardiographic parameters of the R21C KI mice will have to be examined to clearly determine whether the mutant gene dosage alters the severity of the R21C HCM phenotype in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of the HCM phenotype does not seem to be dependent on the R21C mutant gene dosage because ϳ25% of the total cTnI is mutated in the heterozygotes and is sufficient to promote a similar hypertrophic response to that of the homozygous mice. Nevertheless, previous studies have shown that an increase in the ratio of mutant to WT protein in vivo and in vitro within myofilaments can lead to larger phenotypic and/or lethal effects (43). Therefore, in vivo hemodynamic and echocardiographic parameters of the R21C KI mice will have to be examined to clearly determine whether the mutant gene dosage alters the severity of the R21C HCM phenotype in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Messer et al (45) demonstrated that in the donor heart samples, the bisphosphorylated species predominated (72.2%); whereas, in diseased hearts, the dephosphorylated species of cTnI predominated (ϳ77%). Notably, phosphorylation of Ser 43 and Thr…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCM TnI R192H, DCM TnT ⌬K210, and ischemia-induced truncated TnI- were chosen to test the hypothesis because they represent different protein (TnI or TnT) modifications (missense mutation, deletion, or truncation) and disease subtypes (familial or acquired) that can afflict both mouse and humans (27,47,48). By engineering TnC with a wide, yet fine-tunable, range of Ca 2ϩ sensitivities, abnormally increased or decreased Ca 2ϩ binding associated with different cardiac dysfunctions can be corrected, and their altered Ca 2ϩ dissociation rates can be reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, for any particular class of inherited cardiomyopathies, the apparent Ca 2ϩ sensitivity of TnC and force development are typically altered in a qualitatively similar manner (20,22,25). Furthermore, pharmacological and genetic interventions that rectify the apparent Ca 2ϩ sensitivity of cardiac muscle in transgenic animal models harboring cardiomyopathic genes show promise of alleviating the disease symptoms (27)(28)(29). For instance, modulating TnI, TnT, or tropomyosin (each of which can indirectly tune the Ca 2ϩ sensitivity of TnC) counteracted the abnormal cardiac muscle Ca 2ϩ sensitivities and ameliorated the disease symptoms (28 -30).…”
mentioning
confidence: 99%